Indoor air-related symptoms and volatile organic compounds in materials and air in the hospital environment. Issue 5 (3rd September 2019) - Rautiainen, Paavo; Hyttinen, Marko; Ruokolainen, Joonas; Saarinen, Pekka; Timonen, Jussi; Pasanen, Pertti
ABSTRACT: In this case study, hospital workers did suffer from symptoms related to the poor indoor air quality. To investigate reasons for symptoms MM40-survey and house inspection methods were performed. The study consisted of 49 operating rooms and 470 employees. MM-40 survey revealed that over 40% of the staff suffered from skin reactions, over 50% had upper respiratory tract symptoms and 25% suffered headaches. No reason for the staff's symptom could be found in the structural studies of workplaces. The mean air exchange rate of the rooms was 5.51/h. In total 61 materials and 49 indoor air samples were taken. The most frequently found compounds in the material samples were 2-ethyl-1-hexanol and aliphatic hydrocarbons. VOC emissions were high in some of the material samples and they presumably were the one reason for the workers' symptoms observed in some in of the rooms. However, indoor air VOC concentrations were low in most of the cases. According to the linear regression model emissions from flooring material couldn't explain the indoor air concentration of the VOCs. One reason for that was the high ventilation rates of the rooms, which presumably kept VOC levels in indoors low. In addition, VOC concentrations indoors were strongly related to the ongoing healthcare activities in the hospital.